Microorganisms isolated from cultures and infection focus and antibiotic treatments in febrile neutropenic children from Sanliurfa, Turkey - (:unkn) unknown (TURKISH J PEDIATRICS, 2016)
Chemotherapy induced febrile neutropenia predisposes patients to life threatening infections. We aimed to determine the causative microorganisms, infection focus and antibiotic treatment success in febrile neutropenic children with leukemia. A total of 136 febrile neutropenic episodes in 48 leukemic children were reviewed retrospectively from records. Among 136 febrile neutropenic episodes, 68 (50%) episodes were microbiologically documented. Methicillin sensitive coagulase (-) Staphylococcus aureus were the most common isolates from hemoculture (20.5%). The most frequently documented infection focus was mucositis (31.9%). Ceftazidime plus amikacin was the most commonly used antimicrobial treatment for the empirical therapy (52.9%). The overall response rates were 70.5%, 86.9%, and 66.6% of first line, second line and third line therapies, respectively. The spectrum of isolates among febrile neutropenic children in our hematology clinic appears to be gram positive pathogens which are the most common agents. Therefore the, documentation of the flora in each unit could help to decide appropriate empirical therapy which is life saving.
Keywords: child; leukemia; fever; neutropenia; empiric therapy; CEFTAZIDIME PLUS AMIKACIN; COMBINATION THERAPY; PEDIATRIC-PATIENTS; GRANULOCYTOPENIC PATIENTS; EMPIRIC THERAPY; SINGLE-CENTER; SOLID TUMORS; CANCER; MONOTHERAPY; MEROPENEM